Dynamic evolution of edge dislocation and its effect on bcc-hcp martensitic transformation in dual-phase high-entropy alloy. (December 2021) - Song, Zhicheng; Lin, Yicheng; Wang, Peng; Li, Qianqian
Abstract: The interactions between phase transformation and dislocation determine the evolution process of microstructures in dual-phase high-entropy (DP-HEA) alloy. However, due to rapid evolution process in martensitic transformation (MT) and the lack of corresponding atomic-scale simulation method, the dynamic evolution processes of dislocation in MT are not yet fully understood. In this work, molecular dynamics (MD) simulation is employed to study the atomic-scale dynamic evolution of edge dislocations and its effect on MT in Ta0.5 HfZrTi. The simulation results reveal that the gliding of dislocations to the surface decreases the MT nucleation stress due to increased stress concentration. For the higher global stress (8.0 GPa), the growth of the martensitic variant is found impeded by the new martensitic variant produced near the dislocation core. For the lower global stress (7.1 GPa), the preset edge dislocation will migrate due to elastic strain's incompatibility between dislocation core and phase boundary. Highlights: Observation of the dynamic evolution of edge dislocation and its effect with MD simulation. Capturing the atomistic details of the martensitic transformation and dislocation in Ta0.5 HfZrTi. Investigation of the effect of stress level on the dynamic evolution of dislocation in the deformation process.